UKRAINIAN-RUSSIAN STATE BORDER: PROBLEMS OF FORMATION, PROTECTION AND SECURITY - Доценко, Анатолій (Human Geography Journal, 2015)
The paper identified four stages in the formation of modern Ukrainian-Russian border, and marked changes in administrative-territorial structure of the northern and south-eastern Ukrainian border. Formation of the state border in eastern Ukraine was quite lengthy, difficult and complex process in which the significant role played by subjective factors. Border security is considered as part of the national security of Ukraine, which also includes border security. The article deals with ethnic and geographic and geopolitical aspects of the formation of the eastern border. Along with the realization of the state of the "The Wall" we offer a number of important steps to strengthen and secure the protection of Ukrainian-Russian border to illegally cross the Russian terrorists and military units.